Implementation of pediatric allergic rhinitis module as a part of AETCOM among first-year medical undergraduates: Mixed methods evaluation - Nihar Ranjan Mishra; Prakash Y Peralam; Amol R Dongre; Ramji Singh; Kalyan Goswami; Biswabina Ray; Late Major Kuravi Nagaraju; Debangshu Ghosh; Jayasri Patra; Prabrajika Vivekprana (Wolters Kluwer Medknow Publications, 2023)
Background: Children suffering from allergic rhinitis (AR) in their earlier days of life, not receiving proper treatment, subsequently develop asthma. To sensitize the first-year medical undergraduates about AR by implementing pediatric allergic rhinitis (PAR) module as a part of their attitude, ethics, and communication (AETCOM) curriculum. Materials and Methods: Triangulation type of mixed method study was conducted from January 2021 to June 2021 among 125 first-year medical undergraduate students. The PAR module communication checklist was developed and validated by an interprofessional (IP) team. Twenty multiple-choice questions (MCQs) were framed for both pretest and posttest cognitive assessment of the students. The pretest assessment was done (first 15 min) followed by the teaching of the PAR module (30 min), and lastly the posttest assessment along with open-ended feedback (last 15 min). Objective Structured Clinical Examination (OSCE) communication checklist along with the guidelines was given to the observer during the student-patient encounter to score the learner and to assess the communication skill. Apart from descriptive analysis, paired t-test and content analysis were done. Results: A statistically significant difference in the mean scores before and after the PAR module and communication checklist (P < 0.001). Majority (78/81, 96%) of the students favored this module, while (28/81) 34.6% suggested modifications. Most of the parent's feedback was good about the student's communication skill in terms of empathy (118), behavior (107), and greet (125); however, 33 parents were about the opinion of difficulties in closing the session, 17 parents commented about student's language problem and 27 about feedback. Conclusion: The PAR module should be taught in the current medical curriculum as a part of AETCOM in the foundation course as early clinical exposure with some modifications in the existing module.